2020
DOI: 10.18280/ijht.380106
|View full text |Cite
|
Sign up to set email alerts
|

Approximation Methods for Analysis and Formation of Mechanisms for Regulating Heat and Mass Transfer Processes in Heat Equipment Systems

Abstract: The need to increase the accuracy of decisions and the depth of analysis of complex heat power systems determines the relevance of modeling and regulation of heat and mass transfer processes with the development of theoretical models and the development of a new methodology. Uncertainty of the environment increases the significance of the problems of insufficient efficiency of the available numerical approaches to the modeling of dynamic processes and the regulation of heating elements. Therefore, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In other words, for any values of the parameter (even arbitrarily large, but finite values) there will always be ω < ω 1 for which the values of the function constructed by Kotelnikov will differ from π, and there will always be ω > ω 1 , for which its values will be non-zero. Moreover, it is important to note that the indicated difference with increasing T does not tend to zero, but to approximately 0.281 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Mathematical tools for approximating functions make it possible to evaluate and more accurately control jump-like processes.…”
Section: New Methods For Approximating Step Processes: Functions By T...mentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, for any values of the parameter (even arbitrarily large, but finite values) there will always be ω < ω 1 for which the values of the function constructed by Kotelnikov will differ from π, and there will always be ω > ω 1 , for which its values will be non-zero. Moreover, it is important to note that the indicated difference with increasing T does not tend to zero, but to approximately 0.281 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Mathematical tools for approximating functions make it possible to evaluate and more accurately control jump-like processes.…”
Section: New Methods For Approximating Step Processes: Functions By T...mentioning
confidence: 99%
“…Alyukov et al [5][6][7][8][9][10][11] make it possible to predict the influence of individual factors on the operation of an enterprise as a whole. V. Balakrishnan et al, A. Alabugin, and A. Nikitin showed that new control algorithms with increased accuracy significantly reduce the impact of forecasting errors [12][13][14]. In the economic ecosystems of a number of developing countries, researchers have identified the insufficient decarbonization of industrial territories.…”
Section: Introductionmentioning
confidence: 99%
“…At many domestic enterprises of industrial heat and power engineering, evolutionary methods of modernization of individual elements of equipment with a low level of innovation of technologies and results prevail. Investment decisions on new construction and technical re-equipment projects are often made without modeling the processes of transition to technologies and organizational methods of energy saving based on the factors of the new industrial revolution [22].…”
Section: Methodologies Of Modeling Processes Combining Generation Of ...mentioning
confidence: 99%
“…In such a digital economy, it is necessary to use open educational platforms based on large databases [21]. Especially they are necessary for analyzing the possibilities of advanced combination of resources based on the organization of ETC with the inclusion of objects of distributed energy, other multipurpose productions and participation in projects of such transformation of research and educational complexes of type 4.0 [22,23]. The considered methods solve a complex of problems of the organization of processes of high-tech development with use of integration of the diversified resources.…”
Section: Literature Reviewmentioning
confidence: 99%